IDENTIFIKASI PENYEBAB PENYAKIT LODOH PADA SEMAI KALIANDRA (Calliandra callothyrsus) - Nur Hidayati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2018)
Seedling quality is one of factors determining the success of forest management. Pathogen attack that causes disease in the nursery is one reason hindering the target of seedling provision. Therefore, disease outbreak in the nursery need to be properly studied to set precautionary or control measures. The aim of this study is to isolate and identify causes of damping off which cause the death of kaliandra (Calliandra callothyrsus) seedlings. A number of kaliandra seedlings from 30 gram seed of kaliandra, died due to damping off disease. Dead seedling samples were isolated then observed macroscopically and microscopically (examined under the microscope). Koch Postulate test was conducted to identify the disease causing the death of kaliandra seedlings. Identification results indicate that the causes of damping-off disease are Fusarium sp. and Rizoctonia solani.